Design, synthesis and biological evaluation of quinoxaline compounds as anti-HIV agents targeting reverse transcriptase enzyme - Fabian, Lucas Emanuel (2020)
Infection by human immunodeficiency virus still represents a continuous serious concern and a global threat to human health. Due to appearance of multi-resistant virus strains and the serious adverse side effects of the antiretroviral therapy administered, there is an urgent need for the development of new treatment agents, more active, less toxic and with increased tolerability to mutations. Quinoxaline derivatives are an emergent class of heterocyclic compounds with a wide spectrum of biological activities and therapeutic applications. These types of compounds have also shown high potency in the inhibition of HIV reverse transcriptase and HIV replication in cell culture. For these reasons we propose, in this work, the design, synthesis and biological evaluation of quinoxaline derivatives targeting HIV reverse transcriptase enzyme. For this, we first carried out a structure-based development of target-specific compound virtual chemical library of quinoxaline derivatives. The rational construction of the virtual chemical library was based on previously assigned pharmacophore features. This library was processed by a virtual screening protocol employing molecular docking and 3D-QSAR. Twenty-five quinoxaline compounds were selected for synthesis in the basis of their docking and 3D-QSAR scores and chemical synthetic simplicity. They were evaluated as inhibitors of the recombinant wild-type reverse transcriptase enzyme. Finally, the anti-HIV activity and cytotoxicity of the synthesized quinoxaline compounds with highest reverse transcriptase inhibitory capabilities was evaluated. This simple screening strategy led to the discovery of two selective and potent quinoxaline reverse transcriptase inhibitors with high selectivity index.